Case Report: Successful treatment of late-onset immune checkpoint inhibitor-associated membranous nephropathy in a patient with advanced renal cell carcinoma - Ratanasrimetha, Praveen; Reddy, Vikas D.; Kala, Jaya; Tchakarov, Amanda; Glass, William F.; Msaouel, Pavlos; Lin, Jamie S. (Frontiers in Immunology, 2022)
Background: Diagnosing immune checkpoint inhibitor (ICI) associated nephritis can be challenging since they are rare complications of therapy, associated with a spectrum of immune-mediated pathologies, and can present months after ICI therapy discontinuation (i.e. late-onset). ICIs are increasingly administered in combination with other cancer therapies with associated nephrotoxicity further obfuscating the diagnosis of ICI-associated nephritis. In this report we describe the first suspected case of late-onset ICI-associated membranous nephropathy (MN) in a patient with metastatic clear cell renal cell carcinoma (RCC) who had discontinued ICI therapy 6 months prior to presentation. Prompt recognition of the suspected late-onset immune related adverse event (irAE) resulted in successful treatment of MN and continuation of RCC therapy. Case presentation: A 57-year-old male with metastatic clear cell RCC was responsive to third line RCC therapy with lenvatinib (oral TKI) and everolimus (oral mTOR inhibitor) when he presented with nephrotic range proteinuria and acute kidney injury (AKI). His kidney biopsy revealed probable secondary membranous nephropathy (MN) with subendothelial and mesangial immune complex deposits and negative staining for both phospholipid A2 receptor (PLA2R) and thrombospondin type-1 domain-containing 7A (THSD7A). While a diagnosis of paraneoplastic MN could not be excluded, the patient was responding to cancer therapy and had tumor regression. However, six months prior to presentation, the patient had received pembrolizumab, an ICI, with his first line RCC treatment. Due to concern that the patient may be presenting with late-onset ICI-associated MN, he was effectively treated with rituximab which allowed for his continued RCC therapy. Conclusion: This report highlights a case of suspected late-onset ICI-associated MN and the increasing complexity of recognizing renal irAEs. With the growing indications for the use of ICIs in combination with other cancer therapies, recognizing the various presentations of ICI-immune nephritis can help guide patient management and treatment.